(untitled) (REMUNOM, 2025)
Background: Ecchymosis is frequently present in the postoperative cervicofacial liposculpture surgery, but patients often wish for a way to minimize bruising so that other people do not notice the cosmetic intervention. Objectives: This case report has the objective to stimulate further studies about the use of hyaluronidase in reducing postoperative ecchymosis. Article design and setting: In this article we show two case reports of patients that had cervicofacial liposculpture surgery and the satisfactory outcome of using hyaluronidase. Results and conclusion: Hyaluronidase seems to be efficient in the case report, in agreement with reports in the literature regarding the use of hyaluronidase as means of promoting the reabsorption of subcutaneous hematomas.